ANALISA PERSEPSI RASA BANGGA ORANG INDONESIA TERHADAP REPRESENTASI BUDAYA INDONESIA DALAM SEBUAH VIDEO GAME - Ardiansyah; Robin (P3M Institut Teknologi Pagar Alam, 2023)
The rapid development of technology in the era of the industrial revolution provided changes in all aspects of human life. Digital games are an example in terms of social and cultural aspects that give color to the life of every individual in their activities. A few years ago, digital games were just entertainment for some people. Nowadays, digital games have even become a reality that cannot be separated from the activities of all ages. Culture is the only value planted by creators in producing a video game. For example, the Mobile Legends game features the character Gatot Kaca as a character in battle and Indonesia's endemic animal, the Komodo dragon in the game Far Cry. Entertainment media is expected to be able to provide further education and introduction to a culture that is incorporated into the flow of the game. With the appointment of Indonesian culture in local and international games, the author will examine further the sense of nationalism of the Indonesian people.